INSENSITIVITAS GENDER DAN EKSKLUSI SOSIAL BAGI PASANGAN NIKAH USIA ANAK: PENDEKATAN FENOMENOLOGI DI KECAMATAN RANUYOSO KABUPATEN LUMAJANG - Hidayah, Ulil; Luayyin, Reza Hilmy (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2024)
This research aims to explore the gender insensitivity and social exclusion experienced by child marriage couples in Ranuyoso sub-district, Lumajang district. Using a phenomenological approach, the study collected data through in-depth interviews with child marriage couples, parents and community leaders, to understand their experiences and the challenges they face in the local social and cultural context. The results show that gender insensitivity, manifested in traditional norms and values, contributes to the social exclusion of child marriage couples. They often face constraints in accessing education, health services and participation in community activities. This research reveals that low awareness of gender issues exacerbates their exclusion and limits their opportunities for social and economic development. The findings highlight the importance of interventions based on sensitive gender understanding and community support to improve social inclusion for child marriage partners in the area.